N_LyST: a simple and rapid screening test for Lynch Syndrome - Susanti, Susanti; Fadhil, Wakkas; Ebili, Henry O.; Asiri, Abutaleb; Nestarenkaite, Ausrine; Hadjimichael, Efthymios; Ham-Karim, Hersh A.; Field, Joanne; Stafford, Katherine; Matharoo-Ball, Balwir; Hassall, James C.; Sharif, Abid; et al. (BMJ Publishing Group Ltd, 2018)
Aims: We sought to use PCR followed by high-resolution melting (HRM) analysis to develop a single closed-tube screening panel to screen for Lynch Syndrome. This comprises tests for microsatellite instability (MSI), MLH1 methylation promoter and BRAF mutation. Methods:For MSI-testing, 5 mononucleotide markers (BAT25, BAT26, BCAT25, MYB, EWSR1) were developed. In addition, primers were designed to interrogate Region C of the MLH1 promoter for methylation (using bisulphite-modified DNA) and to test for mutations in codon 600 of BRAF. Two separate cohorts from Nottingham (n = 99, 46 with MSI, 53 being microsatellite stable (MSS)) and Edinburgh (n=88, 45 MSI, 43 MSS). Results:All the cases (n=187) were blind tested for MSI and all were correctly characterised by our panel. The MLH1 promoter and BRAF were tested only in the Nottingham cohort. Successful blinded analysis was performed on the MLH1 promoter in 97 cases. All MSS cases showed a pattern of non-methylation whilst 41/44 cases with MSI showed full methylation. The three cases with MSI and a non-methylated pattern had aberrations in MSH2 and MSH6 expression. BRAF mutation was detected in 61% of MSI cases and 11% of MSS cases. Finally, 12 cases were blind screened by using the whole panel as a single test. Of these, 5 were identified as MSS, 4 as MSI/non-LS and 3 as MSI/possible LS. These results were concordant with the previous data. Conclusion: We describe the Nottingham Lynch Syndrome Test (N_LyST). This is a quick simple cheap method for screening for Lynch Syndrome.